2015
DOI: 10.3389/fchem.2015.00061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the side effects of poly(epsilon-caprolactone) nanocapsules containing atrazine toward maize plants

Abstract: Poly(epsilon-caprolactone) (PCL) nanocapsules have been used as a carrier system for the herbicide atrazine, which is commonly applied to maize. We demonstrated previously that these atrazine containing polymeric nanocapsules were 10-fold more effective in the control of mustard plants (a target species), as compared to a commercial atrazine formulation. Since atrazine can have adverse effects on non-target crops, here we analyzed the effect of encapsulated atrazine on growth, physiological and oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…Additionally, no effects were observed after treatment with NC, compared to the control (Fig. 5), in agreement with previous studies that showed that unloaded PCL nanocapsules did not affect the physiological parameters of maize and mustard plants 45, 46 . The absence of an effect of the nanoformulations without neem oil, used as negative controls, indicates that the inert materials used in the encapsulation process did not cause adverse effects 47 .
Figure 5Net photosynthesis and stomatal conductance of maize plants 1 and 8 days after treatment with the NC_20, NC_15, NC_10, and NC formulations, or with water (control).
…”
Section: Resultssupporting
confidence: 92%
“…Additionally, no effects were observed after treatment with NC, compared to the control (Fig. 5), in agreement with previous studies that showed that unloaded PCL nanocapsules did not affect the physiological parameters of maize and mustard plants 45, 46 . The absence of an effect of the nanoformulations without neem oil, used as negative controls, indicates that the inert materials used in the encapsulation process did not cause adverse effects 47 .
Figure 5Net photosynthesis and stomatal conductance of maize plants 1 and 8 days after treatment with the NC_20, NC_15, NC_10, and NC formulations, or with water (control).
…”
Section: Resultssupporting
confidence: 92%
“…The use of nanoencapsulated atrazine would, therefore, enable the application of lower doses of the herbicide; this could result in reduced release of atrazine into the environment and, in this way, decreased effects on non-target organisms. Oliveira et al (2015b) demonstrated that atrazine-containing PCL nanocapsules had no persistent toxic effects on maize plants, a crop where atrazine is widely applied for weed control. Despite small effects on oxidative stress and photosynthetic parameters that were detected in maize leaves after treatment with the nanoherbicide, these effects were transient and shoot growth remained unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this nanoformulation showed reduced toxicity toward some non‐target organisms, such as the human cells, the algae Pseudokirchneriella subcapitata and the fish Prochilodus lineatus , compared with non‐nanoherbicide . The nanoencapsulation improved the post‐emergence herbicidal activity of atrazine against target species ( Brassica juncea , Bidens pilosa and Amaranthus viridis ), whereas the growth of maize plants was not affected . Therefore, in comparison with the non‐nanoherbicide, a tenfold reduction in atrazine dosage was enabled when atrazine‐containing PCL nanocapsules were applied for the post‐emergence control of target plants .…”
Section: Introductionmentioning
confidence: 97%
“…14,18,19 The nanoencapsulation improved the post-emergence herbicidal activity of atrazine against target species (Brassica juncea, Bidens pilosa and Amaranthus viridis), whereas the growth of maize plants was not affected. [20][21][22] Therefore, in comparison with the non-nanoherbicide, a tenfold reduction in atrazine dosage was enabled when atrazine-containing PCL nanocapsules were applied for the post-emergence control of target plants. 20,22 This would result in an enormous decrease in atrazine input to the environment without compromising weed control.…”
Section: Introductionmentioning
confidence: 99%